Baie James: Institutionalisierung einer indigenen Region - Dörrenbächer, Peter (ERDKUNDE, 1998)
In the middle of the 1970s the James Bay Cree and the Inuit of Northern Quebec have signed the historic James Bay and Northern Quebec Agreement. This first modern and comprehensive treaty between indigenous nations and institutions of the Canadian state was related to the development of the hydroelectric potential of the James Bay area by the public utility Hydro-Quebec. It was the basis for the development of indigenous self-government structures at the regional and local level and for the evolution of a region which is controlled and administered at least partly by the indigenous population. This process of spatial differentiation and institutionalization will be reconstructed on the basis of a model which will be outlined in this paper. It combines reflections on the interrelations of different social, spatial and temporal levels of scale with Paasi's conception of the instutionalization of regions. The process of institutionalization of an indigenous James Bay region consists of five phases which are characterized as follows: Phase 0: pre-institutionalization; Phase 1: evolution of a clearly defined territory and of rights bound to this territory; Phase 2: establishment of regional organizations and self-government structures; Phase 3: evolution of local self-government structures, decentralization and deconcentration of regional entities, social fragmentation and spatial symbols, and Phase 3+: regional identity and identification, reconciliation of the traditional and modern way of life and of the regional and local level. Resulting from this reconstruction, the James Bay area will be characterized as a triadic region which could become a model for other multi-cultural regions.